Green Prices - Tran, Ngoc Bich; Ley, Eduardo (World Bank, Washington, DC, 2012)
"Getting the prices right" is a good starting point but is not sufficient for achieving environmentally efficient outcomes. Other policy interventions are often necessary to complement pricing policies. Moreover, when pricing is not at all feasible, regulatory and command-and-control policies must be used instead. This paper focuses on three interrelated themes at the core of the pricing problem. First, there is the incorporation of non-marketed activities with environmental consequences into aggregate measures of economic performance: the so-called "green-GDP." Second, there is the problem regarding the reliable estimation of the valuation of the shadow prices that properly reflect environmental externalities. Third, there is the issue of full-cost pricing that requires the pricing of environmental externalities for guiding both individual and public decision-making.